Biomechanical Motion of the Tennis Forehand Stroke: Analyzing the Impact on the Ball Speed Using Biofor Analysis Software - Irawan, Ricko; Azam, Mahalul; Rahayu, Setya; Setyawati, Heny; Soedjatmiko; Adi S; Priyono, Bambang; Nugroho, Anan (Physical Education Theory and Methodology, 2023)
Background. The inefficiency of the forehand stroke technique often stems from suboptimal execution of an athlete’s biomechanical movements. For a forehand stroke to be effective, each biomechanical component – the ankles, knees, hips, shoulders, and elbows – must function in an optimal manner. Disconnection of any of these elements can lead to ineffective technique. High speed, influenced by the racket speed at the point of impact, is a key indicator of a perfect forehand stroke. However, the challenge lies in the fact that an athlete’s movement and ball impact cannot be accurately observed with the naked eye, necessitating specialized tools for analysis. Study purpose. The study aims to develop software that assists in predicting ball speed outcomes based on an athlete’s biomechanical movement during a forehand stroke execution. Materials and methods. The research method employed R&D. Data collection techniques consisted of video recordings of athletes’ forehand strokes, which were later analyzed using software that examines movement angles of 10 national athletes. Results. The results indicated the average angles of elbows = 106.23, shoulders = 153.62, hips = 165.33, knees = 167.63, ankles = 164.54; and ball speed = 199.41 cm/s. Conclusions. The conclusion drawn is that to execute an effective forehand stroke with good ball speed, a moment of inertia must occur at the point of impact. The athletes should bend their elbow slightly, thereby reducing rotational resistance and increasing the speed of the racket head. The ankles, hips, and shoulders must move in synchronization within a continuous coordination chain, thereby allowing the athlete to fully leverage kinetic chain. The flexion movement of the elbow during the forward swing step is more effective than the extension movement where the elbow is slightly bent, resulting in a perfect shot.